ALGORITHM AND SOFTWARE IMPLEMENTATION OF INTERNATIONAL METEOROLOGICAL CODES DECODING METHOD - Kredentsar, Svetlana; Rudas, Sergey; Ivlieva, Hanna (Proceedings of National Aviation University (archive), 2014)
Аn algorithm that can decode the international meteorological code METAR considering all codeelements has been developed. The software implementation of methods for the international meteorological codeMETAR decoding and its representation in understandable for any user format has been created